1996
DOI: 10.1210/mend.10.8.8843411
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation and dimerization functions in the human vitamin D receptor.

Abstract: The C-terminal domain of the human vitamin D receptor (hVDR) is essential for dimerization with retinoid X receptors and for transcriptional activation. To define the dimerization domain of the hVDR, a series of internal deletion mutants of the receptor were prepared beginning within the E domain and extending through the F domain to the C terminus. These mutant receptors were tested for dimerization and transcriptional activities by means of gel shift assay and beta-galactosidase assay, respectively, in a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
1
36
0
1
Order By: Relevance
“…The CYP24 gene is normally induced by 1,25(OH) 2 D 3 in keratinocytes (56); therefore we used a reporter gene with the human CYP24 promoter linked to a luciferase gene (45). The results (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP24 gene is normally induced by 1,25(OH) 2 D 3 in keratinocytes (56); therefore we used a reporter gene with the human CYP24 promoter linked to a luciferase gene (45). The results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…p24-OHaseLuc was constructed by subcloning 5.5 kb of the promoter region (45) of the human CYP24 gene (kindly provided by Drs. S. Christakos and J. W. Pike, New Jersey Medical School and University of Wisconsin, respectively) into a firefly luciferase plasmid, lucp1 (45).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies showed that steroid receptor activation involves conformational changes (2,3), phosphorylation/dephosphorylation (4), interactions with coregulator proteins (2,5,6), and dimerization (7). The activation process of the glucocorticoid receptor (GR), androgen receptor, and progesterone receptor also includes a translocation of these receptors from the cytoplasm to the nucleus.…”
Section: The Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…A 2MD-mediated increase in VDR DNA affinity may result from enhanced VDR interaction with RXR and with coactivators such as SRC-1 and DRIP205, both of which could enhance the stability of the VDR on DNA. Plasmids-The human osteocalcin (OC) promoter reporter plasmid phOC-3900 luc, the human Cyp24 reporter plasmid phCyp24-luc (ph24OHase-luc) and pGal4(5ϫ)-luc were previously reported (20,21). pcDNA-hVDR, phVDR-VP16, and pCH110-␤gal have been also previously described (20,22).…”
mentioning
confidence: 99%
“…Plasmids-The human osteocalcin (OC) promoter reporter plasmid phOC-3900 luc, the human Cyp24 reporter plasmid phCyp24-luc (ph24OHase-luc) and pGal4(5ϫ)-luc were previously reported (20,21). pcDNA-hVDR, phVDR-VP16, and pCH110-␤gal have been also previously described (20,22). pcDNA-hVDR(R417A/R420A) was prepared from pcDNA-hVDR using the QuikChange site-directed mutagenesis kit from Stratagene (La Jolla, CA).…”
mentioning
confidence: 99%